Effect of nAl2O3 on the part density and microstructure during the laser-based powder bed fusion of AlSi10Mg composite. Issue 4 (8th February 2020) - Du, Zhenglin; Chen, Hui-Chi; Tan, Ming Jen; Bi, Guijun; Chua, Chee Kai
Abstract : Purpose: In recent years, additive manufacturing techniques have attracted much research attention because of their ability to fabricate customised parts with complex geometry. The range of composites suitable for laser-based powder bed fusion technique is limited, and has not been investigated yet. This paper aims to study the fabrication of AlSi10 Mg reinforced with n Al2 O3 using the laser-based powder bed fusion technique. Design/methodology/approach: An experimental approach was used to investigate the densification of AlSi10 Mg– n Al2 O3 composites using laser-based powder bed fusion technique. Optimisation of the porosity was performed, and microstructure evolution was evaluated. Findings: In this study, laser volumetric energy density (approximately 109 J/mm 3 ) was found to be required for the fabrication of AlSi10 Mg– n Al2 O3 composites with a relative volumetric density approximating 99%. The use of laser volumetric energy density resulted in larger grains. Columnar grain structure was observed via the use of electron backscatter diffraction mapping. Originality/value: This paper examines the processing of new aluminium composite material suitable for the fabrication via the laser-based powder bed fusion technique.